Desain Ilustrasi Foto Pada Baju Kaos Dengan Media Fotografi Digital Pendukung Pariwisata Budaya Di Pura Tanah Lot Dan Taman Ayun - I Made Saryana; Anis Raharjo; Amoga Lelo Octaviano (Mudra Jurnal Seni Budaya, 2018)
Penelitian ini bertujuan untuk mengembangkan industri kreatif dengan menerapkan fotografi digital melalui pengembangan produk instan dengan desain ilustrasi foto pada baju kaos. Pemilihan Obyek wisata Pura Tanah Lot Tabanan dan Pura Taman Ayun Badung Bali, dijadikan obyek penelitian karena obyek wisata tersebut selalu ramai dikunjungi wisatawan. Pengumpulan data dilakukan dengan observasi, wawancara dan studi pustaka. Data yang diperoleh dari hasil observasi dan wawancara dianalisis dengan menggunakan metode penciptaan seni, sehingga hasil análisis dapat dijadikan pedoman atau konsep dasar dalam pengembangan produk sovenir baju kaos. Penelitian ini dilakukan dengan (1) Mengidentifikasi berbagai jenis sovenir baju kaos yang dijual pada kawasan obyek wisata Tanah Lot Tabanan dan Pura Taman Ayun Badung Bali, baik dari bahan, desain ilustrasinya serta teknik pembuatannya. (2) Menganalisis harga, tingkat penjualan, serta bahan, desain ilustrasinya dan teknik pembuatannya.  (3). Melakukan eksperimen desain ilustrasi foto dengan fotografi digital dan pengolahan melalui komputer. (4) Pembuatan ilustrasi foto dan menerapkannya dengan fotografi dan sablon digital pada baju kaos.This research started with observation of several tourism destinations  in Bali such as Tanah Lot in Tabanan and Taman Ayun Badung. The observation is that by taking pictures of tourists and then selling it on photo printed  paper, profit margins are minimized. Furthermore, selling t-shirts as souvenirs on which the design is lacking in representation of the location show restricted and minimized monetization capabilities. Based on these observations, the researcher intends to conduct research while creating an innovative product which is capable of representing the aforementioned locations. Through implementation of digital photography and patternization modalities, designed photos can instantaneously be printed on the t-shirt, and automatically it may be worn by tourists. This technique can prove to have drastic impact upon the profit margins of vendors in comparison to conventional modalities. The aim of the research is to develop creative industry by applying digital photography through the development of instant product through creative design on t-shirts. The option to choose Tanah Lot and Taman Ayun temples because these toruism objects are of the most favorite tourism destinations steadily receive visitation from many tourists from all around the world. This research focuses on (1) The identification of T-shirts as souvenirs sold in Tanah Lot temple in Tabanan and Taman Ayun temple in Badung, based on  fabric, lllustration design and the production techniques. (2) Price analysis, seeling rank, fabric, illustration design and production techniques; (3) To conduct experimental photography llustration design through digital photography and computer-driven image processing; (4) The production of photo llustration and digital patterns on t-shirts. Data collection is taken based on observation, interviews and library research. The data is analyzed using art creation method therefore it can be used as guidance or a basic concept in developing t-shirts as souvenirs